Genetic Mechanism of Lower-Order Faults in Shale Formations in Rift Basins. (19th April 2023) - Yang, Haimeng; Wu, Xuepeng; Liu, Jingshou; Hu, Caifu
Abstract : The distribution of lower-order faults affects the development of oil and gas and the distribution of remaining oil, which is also the key to the development of fault block reservoirs in eastern China. The lower-order faults are characterized by short extension, small fault displacement, and difficult identification by traditional seismic interpretation methods. Therefore, it is necessary to predict the development law of faults in combination with the paleostress field during the fault formation period to improve the accuracy of fault seismic interpretation. In this paper, on the basis of reservoir structural analysis and rock mechanics experiments, the geological and mechanical model of the Sanduo period is established to predict the simulation of the paleostress field during the development of lower-order faults. The development of lower-order faults in rift basins is mainly controlled by the minimum principal stress and stress difference, and the shear stress in the profile controls the tendency of faults. Controlled by the paleostress field, the occurrence of lower-order faults in the Weizhuang area, Gaoyou Sag, and Subei Basin is very complex, and the strike of the fault is distributed as a tension shear broom on the plane. The prediction results can provide a reference for the excavation of remaining oil and the development of oil and gas.